A transparent, solvent-free laminated top electrode for perovskite solar cells. Issue 1 (1st December 2016) - Makha, Mohammed; Fernandes, Silvia Letícia; Jenatsch, Sandra; Offermans, Ton; Schleuniger, Jürg; Tisserant, Jean-Nicolas; Véron, Anna C.; Hany, Roland
Abstract: A simple lamination process of the top electrode for perovskite solar cells is demonstrated. The laminate electrode consists of a transparent and conductive plastic/metal mesh substrate, coated with an adhesive mixture of poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate), PEDOT:PSS, and sorbitol. The laminate electrode showed a high degree of transparency of 85%. Best cell performance was achieved for laminate electrodes prepared with a sorbitol concentration of ~30 wt% per milliliter PEDOT:PSS dispersion, and using a pre-annealing temperature of 120°C for 10 min before lamination. Thereby, perovskite solar cells with stabilized power conversion efficiencies of (7.6 ± 1.0)% were obtained which corresponds to 80% of the reference devices with reflective opaque gold electrodes. Abstract :